2008
DOI: 10.1007/s10797-008-9066-z
|View full text |Cite
|
Sign up to set email alerts
|

Tax competition, excludable public goods, and user charges

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…According to research by Bartle et al [2011], user charges have grown from 10.4% of total revenues in 1975 to 15.7% in 2007: Borge [2000] even indicates that the increasing importance of these revenues to local governments' budgets is an international trend, and the relationship between user charges and other sources of public revenues have been discussed for years. Huber and Runkel [2009] came to similar conclusions in their study. They indicate that user charges for public services in recent decades have become very significant despite the continued dominance of taxes; an example is a share of user charges in the federal budget revenues, where the share of payments increased from 8.8% (fiscal year 1976-1977) to 10.5% (fiscal year 1991-1992) and at the local level from 10.7% (fiscal year 1976-1977) to 15.3% (fiscal year [2000][2001].…”
Section: Literature Reviewsupporting
confidence: 80%
See 1 more Smart Citation
“…According to research by Bartle et al [2011], user charges have grown from 10.4% of total revenues in 1975 to 15.7% in 2007: Borge [2000] even indicates that the increasing importance of these revenues to local governments' budgets is an international trend, and the relationship between user charges and other sources of public revenues have been discussed for years. Huber and Runkel [2009] came to similar conclusions in their study. They indicate that user charges for public services in recent decades have become very significant despite the continued dominance of taxes; an example is a share of user charges in the federal budget revenues, where the share of payments increased from 8.8% (fiscal year 1976-1977) to 10.5% (fiscal year 1991-1992) and at the local level from 10.7% (fiscal year 1976-1977) to 15.3% (fiscal year [2000][2001].…”
Section: Literature Reviewsupporting
confidence: 80%
“…Direction Source TAXES Positive • From 1987 to 1997, reliance on user changes continued to increase steadily, but overall revenue diversification appears to have slowed [Hendrick, 2002] • (…) less diversification among towns compared to states and municipalities because of a sustained reliance on property taxation over time [Carroll, Johnson, 2010] • The incentive to impose user charges is larger, the higher the intensity of tax competition measured by the number of countries competing over mobile capital [Huber, Runkel, 2009] TAXPOWER Positive • Implementation of user charges is motivated by limiting taxes and expenditures [Sun, Jung, 2012] SALARIES Positive • User charges for kindergartens rise simultaneously with household income but decrease with municipal revenues. User charges for elderly and disabled care rise simultaneously with household income [Aaberge, Langøren, 2006] • Revenues variation is dependent on many factors among which the most important is household income [Carroll, 2009] DEBT Positive • Polish law on public finance 2 • Dynamics of changes in the level of revenues is important for the level of a new debt ceilings [Werwińska, 2014] • Maintaining lower tax rates can continue to be a problem more important than issues related to the financing costs of debt service.…”
Section: Variablementioning
confidence: 99%
“…For example, recent extensions have examined the role played by imperfect competition and economic rents, 16 Note that these arguments do not apply for benefit taxes for services provided to mobile capital or taxes designed to compensate for external costs imposed by mobile capital. 17 On the other hand, tax competition may restrain "Leviathan" tendencies for overconsumption of public services and encourage governments to use desirable user charges and benefit taxes (McLure, 1986;Edwards and Keen, 1996;Huber and Runkel, 2004). See Wilson (1999), Fuest, Huber and Mintz (2003), Wildasin and Wilson (2004) and Zodrow (2003) for discussions of the negative and positive aspects of tax competition.…”
Section: A Theoretical Models Of Tax Competitionmentioning
confidence: 99%
“…Moreover, they are built on the assumption that consumers can adjust their use in response to price changes, as there is a quid pro quo relationship. Huber and Runkel (2004) have shown that road user charges are efficient for congestible public goods and for public goods with negative externalities, such as traffic congestion and pollution. Hellwig (2005 ) discusses efficient financing schemes with cross subsidies.…”
Section: User Chargesmentioning
confidence: 99%